Aggressiveness of Hedera helix L. growing on monuments: Evaluation in Roman archaeological sites and guidelines for a general methodological approach. (3rd September 2017) - Bartoli, F.; Romiti, F.; Caneva, G.
Abstract: Ivy ( Hedera helix L.) growing on monuments is a common issue in the study of nature's relationship with artefacts in the Euro-Mediterranean area. This is due to its pervasiveness and its double role as protective and as deteriogen. We studied the effect of ivy colonization within the archaeological site of Villa of Massentius . We applied a quantitative method derived from monument mapping method by Fitzner, to evaluate deterioration due to ivy colonization on vertical surfaces. Instead, the capping ivy effects was investigated through a multi-parameter evaluation. We recognized three different damage categories: the superficial loss of surface ( W ), ivy residues on wall after the removal event ( I ), and the loss of compact stone fragments ( P / O ). Mean W corresponded to 58% and P / O to 14%. The total damage rate was positively correlated to the amount of ivy cover and to favourable shady conditions. For the capping ivy, we calculated an average loss of 4.34 cm 3 /m 2 and a high level of soil deposit, which led to a secondary ivy colonization process. This paper proposes a contribution to the identification and quantification of ivy deteriogen activity. The application of the proposed method also provides a useful tool for planning restoration activity.